Entre o discurso e a prática: implementação do currículo de História no programa educacional São Paulo faz escola - Giavara, Ana Paula [UNESP]; Barreiro, Iraide Marques de Freitas [UNESP] (My University, 2014)
In the ambit of educational program São Paulo faz escola (2008-2012), this article offers a critical view of the proposal and implementation of History curriculum in two different schools at São Paulo countryside. It starts with the curricular remodeling occurred in the 80’s and intents to chart a path for discussions involving modern History teaching. In order to achieve this goal, this article uses documents from the curricular restructuration made by the State Department of Education, testimonies of educational subjects and observations of school’s daily routine. It shares the cultural perspective of school analysis, which gives authenticity to the actions of its subjects and it inquiries how History teachers and school administrators participated in the elaboration and implementation of said curriculum

No âmbito do programa educacional São Paulo faz escola (2008-2012), este artigo oferece ao leitor uma visão crítica acerca do processo de proposição e implementação do currículo de História em duas escolas públicas do interior paulista. Partindo da reforma curricular paulista da década de 1980, busca delinear uma trajetória para as discussões acerca do ensino de História na contemporaneidade. Para tanto, utiliza documentos da reestruturação curricular elaborados pela Secretaria da Educação estadual, depoimentos dos sujeitos educacionais, bem como observações do cotidiano escolar. Partilha da perspectiva cultural de análise da escola, que confere autenticidade às ações de seus sujeitos e interroga como professores de História e gestores escolares participaram do processo de elaboração e implementação do referido currículo.
Between speech and practice: the implementation of History curriculum in educational program São Paulo faz escola
Keywords: Curricular reform; History teaching; São Paulo faz escola; Reforma curricular; Ensino de História; São Paulo faz escola